RANCANG BANGUN ALAT PENDETEKSI KESEIMBANGAN TUBUH MANUSIA - Kurniawati, Ana (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2011)
The balance of the human body detector, which is intended to assist in the medical field, will generate information that can analyze the symptoms of a disease caused by a disturbance such as a sense of balance is not balanced, the head felt light, almost fainting and vertigo. The balance of the human body detector consists of a platform which has three sensors. The third sensor will produce a swing movement patterns of the human body. Keywords: Body Balance Detection Equipment